(untitled) (Research, Society and Development, 2023)
Sodium hypochlorite is an endodontic irrigant that repair asepsis to the root canal system, eliminating pathogenic microorganisms and restoring tooth function by promoting increased dentin permeability.The Vickers hardness of dentin was compared in relation to the concentration of sodium hypochlorite. Five upper first molars with 3 roots were chosen. The mesiobuccal roots were immersed in 0.9% saline solution (control). The distobuccal roots were instrumented with 0.5% sodium hypochlorite and the palatine roots with 4.94% sodium hypochlorite. In the statistical analysis, tables and graphs were used to show the research results and the behavior of the data. Descriptive statistics such as mean (x̅), standard deviation (SD) and coefficient of variation (CV) were presented. If CV≤ 15%, the data is considered homogeneous, if 15% < CV < 30%, medium dispersion is considered, and if CV ≥ 30%, the data is considered heterogeneous. To test normality “Kolmogorov-Smirnov” test (K-S test) will be used. And, finally, as a statistical inference, to compare two samples (Groups), Student’s "t" parametric test will be used, if the data are normal, otherwise, the non-parametric "Manny Whitney" test ("U Test") makes the comparisons. It is important to emphasize that all tests were calculated with a significance level of 5%, corresponding to a confidence level of 95% and the program used was Bioestat 5.0. They observed a smaller numerical variation in the mean Vickers hardness on the dentin surface of the samples from group III (4.94% sodium hypochlorite) in the middle and apical thirds in relation to the mean cervical third, an event that was verified in groups I (0.9% saline solution), however, in groups II (0.5% sodium hypochlorite) there was a greater numerical variation in the middle and apical thirds in relation to the cervical third. However, for group III (4.5% sodium hypochlorite) 94%) points to greater Vickers microhardness in the cervical third, while in the middle and apical thirds they found lower microhardness on the dentin surface.